Comparative Study on Two Types of Nonpillar Mining Techniques by Roof Cutting and by Filling Artificial Materials - Enze Zhen; Yubing Gao; Yajun Wang; Siming Wang (Advances in Civil Engineering)
Gob-side entry retaining is an environmentally friendly nonpillar mining technology with high efficiency and safety. With the continuous exploration of the gob-side entry retained by filling (GERF) with roadside supports, the GERF has enabled nonpillar mining. However, dense roadside supports or filled artificial pillars become subject to the pressure of roof pressure instead of coal pillars, which causes problems. Recently, an original innovative gob-side entry retaining technology by roof cutting and pressure relief (RCPR) was developed and extensively implemented in China’s coal production. The gob-side entry formed by different retaining methods has exhibited some differences in the strata behaviors and the results of retained roadways. Via industrial case and numerical simulation, this study explored the influence of entry retaining methods on the results of the entry retained. The results indicate that the total deformation of the surrounding rock of the GERF is larger and more severe; the convergence between the roof and floor and the entry sides displacement is 885 mm and 216 mm, respectively; the hydraulic support pressure near the retained entry is larger; and the peak value is 38.7 MPa. The deformation of the surrounding rock by RCPR is relatively small; the convergence between the roof and the floor and the entry sides displacement is 351 mm and 166 mm, respectively; the hydraulic support pressure near the retained entry is weakened to a certain extent; the peak value is 32.2 MPa; and the peak pressure is reduced by 16.8% compared with the GERF. A numerical simulation analysis reveals the following findings: RCPR changes the surrounding rock structure of a gob-side entry, optimizes the surrounding rock stress environment, and belongs to active pressure-relief entry retaining; the GERF does not adjust the surrounding rock structure of a gob-side entry and belongs to passive pressure-resistance entry retaining; and the surrounding rock of a gob-side entry is significantly affected by pressure. These two methods of gob-side entry retaining have different effects on the surrounding rock of the entry retained. This study can contribute to an exploration of the strata behaviors and the results of a retained roadway by the GERF or RCPR method.